Reducing the time rabbit sperm are held at 5 degrees C negatively affects their fertilizing ability after cryopreservation - Mocé, Eva; Blanch, Eva; Talavan, Amparo; Viudes-De-Castro, María P. (2017)
Cooling sperm to and equilibrating the sperm at 5 degrees C require the most time in any sperm cryopreservation protocol. Reducing the time required for these phases would simplify sperm freezing protocols and allow greater number of ejaculates to be processed and frozen in a given time. This study determined how holding rabbit sperm at 5 degrees C for different lengths of time (0, 10, 15, 20, 30, or 45 minutes) affected the quality of rabbit sperm, measured by in vitro assays, and if reducing the cooling time to only 10 minutes affected the fertilizing ability of the sperm. Reducing the time sperm were held at 5 degrees C to 10 minutes did not affect the in vitro quality of the sperm (percent motile and with intact plasma membranes), although eliminating the cooling phase completely (directly freezing the sperm from room temperature) decreased in vitro assessed sperm quality (P < 0.01). However, reducing the time sperm were held at 5 degrees C, from 45 to 10 minutes, negatively affected the fertilizing ability of sperm in vivo (P < 0.05). In conclusion, completely eliminating cooling rabbit sperm to 5 degrees C before freezing is detrimental for rabbit sperm cryosurvival, and although shortening the time sperm are held at 5 degrees C to 10 minutes does not reduce in vitro sperm quality, it does reduce the fertility of rabbit sperm. Therefore, the length of time rabbit sperm equilibrate at 5 degrees C is crucial to the fertilizing ability of rabbit sperm and must be longer than 10 minutes. Currently, it is not known if holding rabbit sperm at 5 degrees C for less than 45 minutes will affect sperm fertilizing ability. (C) 2014 Elsevier Inc. All rights reserved.